Global Indonesian Diaspora: How many are there and where are they? - Muhidin, Salut; Utomo, Ariane (JAS (Journal of ASEAN Studies), 2015)
In the last few years, there is an increasing interest in connecting Indonesian diaspora around the world in order to assist in the national development. A recent event called â€œCongress of Indonesian Diasporaâ€ held by Indonesian Diaspora Network (IDN) in Jakarta has been conducted to focus on this issue. Nevertheless, there is still little known about the actual size and composition of the global Indonesian diaspora. This paper attempts to contribute to fill in this gap by analysing migration patterns and several specific demographic factors among Indonesian diaspora as part of the largest global community. The paper will also explore the potential impacts of Indonesian diaspora could play in Indonesian development.